2021
DOI: 10.3390/ma14164603
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Exposure to Nickel: Influence on Adhesion and Biofilm Formation on Orthodontic Archwires and Sensitivity to Antimicrobial Agents

Abstract: The presence of nickel could modify bacterial behavior and susceptibility to antimicrobial agents. Adhesion and biofilm formation on orthodontic archwires can be a source of bacterial colonization and possible health hazards. Staphylococcus aureus was subjected to exposure and adaptation to various sub-inhibitory concentrations of nickel. Five strains of bacteria adapted to nickel in concentrations of 62.5–1000 μg/mL were tested for adhesion and biofilm formation on nickel-titanium archwires. Archwires were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Various concentrations of Ni in the orthodontic wire influence the adhesion of Streptococcus mutants. Research by Pavlic et al showed that Ni concentrations of 1000 ug/mL significantly inhibit adhesion [39]. Other research on the prevention of bacteria adhesion on orthodontic wire by applying titanium dioxide has been carried out [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Various concentrations of Ni in the orthodontic wire influence the adhesion of Streptococcus mutants. Research by Pavlic et al showed that Ni concentrations of 1000 ug/mL significantly inhibit adhesion [39]. Other research on the prevention of bacteria adhesion on orthodontic wire by applying titanium dioxide has been carried out [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus strains have developed several resistance mechanisms, especially in patients with chronic antibiotic treatment, in which zirconia restorations are recommended because their surface has a weaker bacterial biofilm formation compared to other biomaterials with limited microorganism adhesion characteristics which can affect the occurrence and progression of oral cavity infections [39] . Adhesion and biofilm formation on orthodontic archwires can be a source of bacterial colonization of Staphylococcus aureus [40] . The results of biofilm-forming capacity indicated that Staphylococcus aureus showed more affinity for stainless steel materials so that control of the surface properties of materials is of crucial importance to prevent biofilm formation on dental materials [34] .…”
Section: Biofilmmentioning
confidence: 99%
“…This phenomenon is demonstrating more interest in bacterial cross‐adaptation and resistance to the antibiotics field, which is caused by exposure to heavy metals. Reduced membrane permeability, activation of the efflux pump, inactivation or mutation of antibiotic and metal target genes along with bacterial adaptability and heavy metal resistance mechanisms, all seem possible [63] …”
Section: Biological Activitymentioning
confidence: 99%
“…Reduced membrane permeability, activation of the efflux pump, inactivation or mutation of antibiotic and metal target genes along with bacterial adaptability and heavy metal resistance mechanisms, all seem possible. [63] The antibacterial investigations revealed that the antibacterial activity was enhanced by the H 2 L ligand alongside a few of its metal chelates. Based on the data, H 2 L ligand generally provided moderate efficacy against Staphylococcus aureus.…”
Section: Antibacterial Activitymentioning
confidence: 99%